An archaeology of persecuted peoples - Scham, Sandra Arnold, author.
1 online resource
Keywords: "This book examines the archaeological evidence for the ancient cultures of the Zagros, Tienshan, Arakan, Hazārajāt, and Gerizim mountains. Through the central questions, what are the most ancient roots of these cultures and why have they persisted in the same locations for so many generations, the book uses material culture to ask why lowland civilizations often have deep-seated prejudices against mountain peoples. The role of religious beliefs and practices is crucial to their story of isolation, tenacity, and resistance in the mountains of Asia and historical and modern approaches are used to analyze the place of religion in highland cultures and discuss the mixture of elements, religious, ethnic and geographical, that characterize the historical trajectories of Asia's disenfranchised mountain minorities. Chapters in the heart of the book explore the archaeology and culture of the Rohingyas, Uyghurs, Hazaras, Kurds, Yazidis, Armenians and Samaritans and the ways they have differed both in the past and today and what that has meant for their way of life. With millions of people still living in mountains today, this book is for archaeologists and anthropologists who are interested both in the distinctive and resilient past of these people but also what that may mean for their future"--